The role of active constituents of in traditional Chinese medicine for primary osteoporosis: a mechanistic review - Song, Chaoqun; Zeng, Lingfeng; Zhao, Changwei (Frontiers in Endocrinology, 2025)
Primary osteoporosis (POP) is a systemic metabolic bone disorder marked by diminished bone density and deterioration of bone microstructure, presenting a considerable challenge to global public health due to its widespread occurrence and heightened fracture risk. Although conventional western pharmaceutical treatments are efficacious, they are often associated with adverse events. Conversely, traditional Chinese medicine (TCM) exhibits distinct potential owing to its multi-targeted and multi-pathway regulatory benefits. This systematic review elucidates the molecular mechanisms of flavonoids, polyphenols, saponins, polysaccharides, coumarins, and alkaloids in the prevention and treatment of POP. The study elucidates the mechanisms of action by modulating critical signaling pathways, including the Wnt/β-catenin, RANKL/OPG pathways and so on, thereby facilitating osteoblast differentiation, suppressing osteoclast activity, and ameliorating oxidative stress, inflammation, and dysbiosis of the intestinal microbiota, ultimately restoring the balance of the bone microenvironment. This research aims to advance the development of innovative POP medications based on TCM principles and to provide scientific validation for individualized therapy.